Черепно-лицевые дефекты плода при синдроме амниотических перетяжек: диагностика, течение и ведение беременности и родов - Дубковский, Г.В.; Демидова, Н.С.; Рыбалка, А.Н.; Аникин, С.С.; Хомуленко, И.А. (Таврический медико-биологический вестник, 2010)
У статті приведено власне спостереження синдрому амніотичних перетяжок, яке привело до виникнення множинних вад розвитку плоду. Обернена увага на складність діагностики даної патології. Описана течія і ведення вагітності і пологів. The article includes our own research of amniotic band syndrome causing numerous foetus congenital malformations. We are drawing attention to the complexity of diagnosing this patology. Controlling the current and monitoring pregnancy and delivery is also described in our article.